The Effect of Psychosocial Support on Healing Time in Leprosy Survivors - Achmad, Luana N.; Tangdialla, Marynda P. I; Harlim, Ago (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Leprosy is a chronic infectious disease caused by Mycobacterium leprae. It can affect the skin, peripheral nerves, and other organs, potentially causing disability if not treated appropriately. In addition to physical impacts, leprosy survivors often experience psychological stress due to social stigma, which can impact healing time. Objective: The purpose of this study was to determine the effect of psychosocial support on healing time among leprosy survivors in the Makassar City Leprosy Village in 2025. Method: This study used a cross-sectional design and was conducted from February to March 2025 using a questionnaire. Total sampling was used to obtain 80 respondents. Univariate and bivariate analyses were performed using chi-square analysis. Result and Discussion: The results showed that 40 respondents (50.0%) had a healing time of ≥ 12 months. Psychosocial support that influences leprosy survivors includes emotional support (attention (p-value = 0.000), empathy (p-value = 0.000), consolation (p-value = 0.000), a place to vent (p-value = 0.000)), instrumental support (financial assistance (p-value = 0.000), resources (p-value = 0.000)), and social support (openness (p-value = 0.000), acceptance (p-value = 0.000), and security (p-value = 0.000)). Conclusions: This study concludes that psychosocial support (emotional, instrumental, and social) significantly influences the recovery time of leprosy survivors in the Makassar City Leprosy Village in 2025.